Alive and Ventilator Free: A Hierarchical, Composite Outcome for Clinical Trials in the Acute Respiratory Distress Syndrome*. Issue 2 (February 2020) - Novack, Victor; Beitler, Jeremy R.; Yitshak-Sade, Maayan; Thompson, B. Taylor; Schoenfeld, David A.; Rubenfeld, Gordon; Talmor, Daniel; Brown, Samuel M.
Abstract : Objectives: Survival from acute respiratory distress syndrome is improving, and outcomes beyond mortality may be important for testing new treatments. The "ventilator-free days" score, is an established composite that equates ventilation on day 28 to death. A hierarchical outcome treating death as a worse than prolonged ventilation would enhance face validity, but performance characteristics and reporting of such an outcome are unknown. We therefore evaluated the performance of a novel hierarchical composite endpoint, the Alive and Ventilator Free score. Design: Using data from four Acute Respiratory Distress Syndrome Network clinical trials, we compared Alive and Ventilator Free to the ventilator-free days score. Alive and Ventilator Free compares each patient with every other patient in a win-lose-tie for each comparison. Duration of mechanical ventilation is only compared if both patients survived. We evaluated power of Alive and Ventilator Free versus ventilator-free days score under various circumstances. Setting: ICUs within the Acute Respiratory Distress Syndrome Network. Patients: Individuals enrolled in four Acute Respiratory Distress Syndrome Network trials. Interventions: None for this analysis. Measurements and Main Results: Within the four trials ( n = 2, 410 patients), Alive and Ventilator Free and ventilator-free days score had similar power, with Alive and Ventilator Free slightly more powerful when a mortality difference was present, and ventilator-free days score slightly more powerful with a difference in duration of mechanical ventilation. Alive and Ventilator Free less often found in favor of treatments that increased mortality and increased days free of ventilation among survivors. Conclusions: A hierarchical composite endpoint, Alive and Ventilator Free, preserves statistical power while improving face validity. Alive and Ventilator Free is less prone to favor a treatment with discordant effects on survival and days free of ventilation. This general approach can support complex outcome hierarchies with multiple constituent outcomes. Approaches to interpretation of differences in Alive and Ventilator Free are also presented. Abstract : Supplemental Digital Content is available in the text.